Development of a performance evaluation tool for end-of-life vehicle management system implementation using the analytic hierarchy process - Raja Mamat, Tengku Nur Azila; Mat Saman, Muhamad Zameri; Sharif, Safian; Simic, Vladimir; Abd Wahab, Dzuraidah (SAGE Publications, 2018)
The management of end-of-life vehicles (ELVs) conserves natural resources, provides economic benefits, and reduces water, air, and soil pollution. In an effort to adequately manage flow of ELVs, modern infrastructure is considered a prerequisite. Thus, development of an effective performance evaluation tool for monitoring and continuous improvement of ELV management systems is strongly desired. In this paper, a performance evaluation tool is proposed for ELV management system implementation, based on the analytic hierarchy process. A real-life case study in Malaysia was conducted in order to demonstrate the potential and applicability of the presented methodology. The scores of eight key success factors in establishing an ELV management system (i.e., management responsibility, performance management, capacity management, resource management, stakeholders’ responsibility, education and awareness, improvement and enforcement, and cost management) are presented. The overall score of the ELV management system implementation in Malaysia is equal to 2.13. Therefore, its performance level is average. The presented multi-criteria decision analysis tool can be of assistance not only to stakeholders in the Malaysian ELV management system, but also to vehicle recycling managers from other countries in order to monitor and continuously improve their ELV management systems.